2012
DOI: 10.1016/j.bmc.2011.11.070
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of protein targets of bioactive small molecules

Abstract: Identification and validation of protein targets of bioactive small molecules is an important problem in chemical biology and drug discovery. Currently, no single method is satisfactory for this task. Here, we provide an overview of common methods for target identification and validation that historically were most successful. We have classified for the first time the existing methods into two distinct and complementary types, the “top-down” and “bottom-up” approaches. In a typical top-down approach, the cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 104 publications
0
33
0
1
Order By: Relevance
“…One way of determining the physiological relevance of a drug target is to see whether there is a pharmacological correlation between the binding of different analogs of the drug to the target and their cellular activity (38). As previously reported, miconazole, terconazole, and fluconazole have IC 50 values for HUVEC proliferation of about 2.5, 7, and >100 μM, respectively (8).…”
Section: Correlation Between Vdac1 Binding and Huvec Inhibition By Itmentioning
confidence: 95%
“…One way of determining the physiological relevance of a drug target is to see whether there is a pharmacological correlation between the binding of different analogs of the drug to the target and their cellular activity (38). As previously reported, miconazole, terconazole, and fluconazole have IC 50 values for HUVEC proliferation of about 2.5, 7, and >100 μM, respectively (8).…”
Section: Correlation Between Vdac1 Binding and Huvec Inhibition By Itmentioning
confidence: 95%
“…In this study, we took a systematic top-down approach to discern the mechanism of action of AglA (Titov and Liu, 2012). Upon assessing its effects on global DNA, RNA and protein synthesis, we observed that AglA inhibited both protein and DNA synthesis without affecting RNA synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…• Complémentation/suppression biochimique dans laquelle un extrait cellulaire est fractionné et les grâce à un ligand immobilisé sur un support ou grâce à un ligand marqué [19,20]. Différentes méthodologies (séquençage, outils immunologiques, analyse protéomique) permettent ensuite d'identifier les protéines liées à la molécule, constituant les cibles potentielles.…”
Section: Recherche De La Cible Par Des éTudes D'identification D'acteunclassified